Toxicity of Single and Mixed Contaminants in Seawater Measured with Acute Toxicity Bioassays - A.R. Fernandez-Alba; L. Piedra; M. Mezcua; M.D. Hernando (The Scientific World Journal)
Different types of organic pollutants commonly detected in seawater have been evaluated by acute toxicity bioassays. Vibrio fischeri, Daphnia magna, and Selenastrum capricornotum were selected to test toxic effects of individual compounds and mixtures of these compounds, obtaining EC50 values in the range of 0.001 to 28.9 mg/l. In the case of mixtures, synergistic toxic responses were seen for a clear majority of the cases (>60%). Mixtures containing methyl-tertiary-butyl ether (MTBE) exhibit accelerated processes that result in a change in concentration required to produce a toxic effect; for example, in the case of mixtures containing MTBE and Diuron and Dichlofluanid.